The role of fine-needle aspiration cytology in papillary thyroid carcinoma cases - Senel, Fatma; Karaman, Hatice (Annals of Medical Research, 2021)
Aim: Thyroid diseases are among the most common diseases in our country and all over the world. Fine-needle aspiration cytology (FNAC) is a useful and simple method for diagnosing papillary thyroid carcinoma (PTC) and can be used as a first step. The aim of this study was to determine the diagnostic value of FNAC in PTC cases by comparing FNAC and histopathological findings and to present our experiences.Material and Methods: This retrospective study evaluates 800 cases who underwent thyroidectomies in our center and had a histopathological examination in the pathology clinic. The age, gender, operation procedure, FNAC findings, and histopathological results of PTC cases were recorded.Results: Of 800 thyroidectomy cases, 119 (14.9%) were diagnosed with PTC; 50 (42%) were classic PTC cases and 69 (58%) were papillary microcarcinoma (PMC) cases. Of the 50 classic PTC cases, 45 had FNAC, which were included in the study. Of these, the positivity rate was 84.5% when atypia of undetermined significance (AUS) cases and suspected malignancies were included with those diagnosed with malignancy. Of 45 PTC cases, 3(6.6 %) were inadequate, 4 (8.9 %) were benign, 7 (15.5 %) were AUS, 4 (8.9 %) were suspected of follicular neoplasm, 18 (40 %) were suspected of malignancy, and 9 (20 %) were diagnosed as malignant. Conclusion: In our study, the false positivity rate was 0.5% and the false negative rate was 8.9%. Carcinomas in the follicular pattern can only be diagnosed by histopathological approach. FNAC is currently the gold standard for diagnosing PTC. However, a benign FNAC diagnosis should be viewed with caution as false-negative results do occur. When a benign FNAC diagnosis is given, surgery is necessary if there is any clinical suspicion of malignancy.
Keywords: Fine-needle aspiration cytology; papillary carcinoma; thyroid